Wirkung von Antiaminosauren auf Trichomonas vaginalis - Christow, Chr. P. (Revista de Biología Tropical, 1973)
B indolilacrylic acid in concentrations above 0.15 mg/ml and styrylacetic acid above 0 20 mg/ml inhibit reproduction of Trichomonas vaginalis. The inconsistent appearance of the round forms of trichomonads may indicate that they are primitive forms that have lost their biological significance in phylogenetic development.